Progressive multifocal leukoencephalopathy in individuals with minimal or occult immunosuppression. Issue 3 (14th October 2009) - Gheuens, Sarah; Pierone, Gerald; Peeters, Patrick; Koralnik, Igor J
Abstract : Background: Progressive multifocal leukoencephalopathy (PML) is a deadly demyelinating disease of the brain, caused by reactivation of the polyomavirus JC (JCV). PML has classically been described in individuals with profound cellular immunosuppression such as patients with AIDS, haematological malignancies, organ transplant recipients or those treated with immunosuppressive or immunomodulatory medications for autoimmune diseases. Methods and case reports: The authors describe five HIV seronegative patients with minimal or occult immunosuppression who developed PML including two patients with alcoholic cirrhosis, one with untreated dermatomyositis and two with idiopathic CD4 + T cell lymphocytopenia. The authors performed a review of the literature to find similar cases. Results: The authors found an additional 33 cases in the literature. Of a total of 38 cases, seven (18.4%) had hepatic cirrhosis, five (13.2%) had renal failure, including one with concomitant hepatic cirrhosis, two (5.2%) were pregnant women, two (5.2%) had concomitant dementia, one (2.6%) had dermatomyositis, and 22 (57.9%) had no specific underlying diagnosis. Among these 22, five (22.7%) had low CD4 + T cell counts (0.080–0.294×10 9 /l) and were diagnosed as having idiopathic CD4 + lymphocytopenia, and one had a borderline CD4 + T cell count of 0.308×10 9 /l. The outcome was fatal in 27/38 (71.1%) cases within 1.5–120 months (median 8 months) from onset of symptoms, and 3/4 cases who harboured JCV-specific T cells in their peripheral blood had inactive disease with stable neurological deficits after 6–26 months of follow-up. Discussion: These results indicate that PML can occur in patients with minimal or occult immunosuppression, and one can revisit the generally accepted notion that profound cellular immunosuppression is a prerequisite for the development of PML.